Probiotic and sodium butyrate in dog food: effects on digestibility and hematological, metabolic and oxidative biomarkers - Schnorr A.M.H.* (2024)
© The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature 2024.Functional additives have been a common practice in dog nutrition, with a focus on animal health. The study's objective was to determine whether using probiotics (Bacillus subtilis and Bacillus licheniformis) and sodium butyrate alone or combined would improve canine health. We used ten non-castrated adults male Beagles separated into four groups were GA) control, GB) 300 mg probiotic/kg of feed, GC) 1000 mg of butyrate/kg of feed, and GD) 300 mg probiotic + 1000 mg butyrate/kg of feed. A crossover model was used, where all animals underwent all treatments; therefore, the experiment was divided into stages of 45 days each (40 days of adaptation and collection of blood samples, and between days 41 and 45, feces were collected to assess digestibility). It is essential to remember that there were 15 days between the stages. Animals from GD had the best apparent digestibility coefficient for dry matter with no effect on other digestibility coefficients. Treatment x day interaction was observed for erythrogram variables; erythrocyte count, hemoglobin concentration, and hematocrit were lower in dogs from GB, GC, and GD than in GA. Animals from GB and GD had a higher concentration of total proteins due to higher levels of serum globulins. There was a treatment x day interaction for glucose, triglycerides, and cholesterol. Serum total antioxidant capacity and total thiols were higher in dogs in the GC and GD groups than in the GA groups. Thiobarbituric acid reactive substances levels were also lower in these groups. These findings suggest that the additives improved canine health more when combined.